PROGRAM KESEHATAN INTERVENSI PENYAKIT JANTUNG DI DESA SUKOREJO NGASEM KABUPATEN KEDIRI - Reny Nugraheni; Gerardin Ranind Kirana, Vivien Dwi Purnamasari (Adiba Aisha Amira, 2022)
The heart is a vital organ for living things. In humans, like other living things, the heart functions to pump blood throughout the body. Risk factors for heart disease are age, gender, heredity or genetics, smoking habits, lack of physical activity, obesity, diabetes mellitus, stress and diet (eating habits or patterns). The method of community service is counseling and demonstration. From the results of community service, the results of knowledge from the pre test-post test questionnaire about heart disease and the benefits of oatmeal from the results of the average pre test - post test score have increased from 90 to 97.5. This shows the effect of providing information on heart disease information and the benefits of oatmeal on public knowledge. The results of knowledge regarding information on heart disease and the benefits of oatmeal obtained from N-Gain indicate that significantly this counseling has a better influence on community knowledge (respondents). It is suggested to the public to reduce the level of rice consumption by replacing the main dish with oatmeal, this can be done at breakfast and dinner. It is better to routinely do physical activity for at least 30 minutes every day, such as walking. And avoid foods that are high in cholesterol and contain bad fats such as fried foods, coconut milk foods, and also regularly consume 5-10 servings of fruits and vegetables per day.